Antimicrobial Photodynamic Therapy for Superficial, Skin, and Mucosal Fungal Infections: An Update - Silva, Laura Beatriz Borim da [UNESP]; Castilho, Ivana Giovannetti [UNESP]; Silva, Fabiana Alves de Souza [UNESP]; Ghannoum, Mahmoud; Garcia, Maíra Terra [UNESP]; Carmo, Paulo Henrique Fonseca do [UNESP] (MDPI, 2025)
The global burden of fungal infections is rising at an alarming rate, with superficial, cutaneous, and mucosal mycoses among the most prevalent. Conventional treatments rely on oral and topical antifungal agents; however, these therapies are often limited by adverse effects, toxicity, frequent recurrence, and poor patient adherence due to prolonged treatment regimens. Moreover, the emergence of antifungal resistance and multidrug-resistant species such as Candidozyma auris and Trichophyton indotineae highlights the urgent need for alternative therapeutic strategies, such as antimicrobial photodynamic therapy (aPDT). aPDT is based on photophysical and photochemical processes involving a photosensitizer (PS), a light source, and molecular oxygen. When combined, these elements generate reactive oxygen species that selectively destroy microbial cells. In this review, we explore various PSs and their effectiveness in aPDT against infections caused by dermatophytes, Candida spp., and other pathogenic fungi. Promisingly, aPDT has demonstrated antifungal activity against both susceptible and resistant strains. In addition, aPDT has been successfully used in cases of mycoses unresponsive to conventional therapies, showing favorable clinical outcomes and overall safety. Current evidence supports aPDT as a valuable strategy for the management of cutaneous, mucosal, and superficial fungal infections and as a potential strategy to combat antifungal resistance.